Phytoplankton Community Dynamic: A Driver for Ciliate Trophic Strategies - Haraguchi, Lumi; Jakobsen, Hans H.; Lundholm, Nina; Carstensen, Jacob (Frontiers in Marine Science, 2018)
Phytoplankton plays a key role as primary producers and mediating biogeochemical cycles in the water column. The understanding of the temporal dynamic of primary grazers channelling energy and carbon from primary producers is important for evaluating aquatic ecosystems functioning. This study investigates the coupling between phytoplankton and ciliates from live samples collected with approximately daily frequency during an almost two-year cycle. The study site is a nutrient-rich temperate estuary, Roskilde Fjord (Denmark). Our aim is to evaluate the importance of protist grazers, especially ciliates, as predators on phytoplankton and to evaluate differences among multiple nutritional strategies through different seasons. The phytoplankton community, was mostly dominated by small organisms (< 20 µm) with few observations of diatoms. In most of observations, heterotrophic dinoflagellates biomass was smaller than biomass of ciliates (< 10%), indicating that ciliates are the main component of microzooplankton. Except for the spring 2016, the ciliate community closely followed the phytoplankton community, showing a tight coupling between the primary producers and grazers during all seasons. This somehow contradicts the general assumption that ciliate dominance is restricted to periods of nutrient limitations dominated by the microbial food web and suggests a year-round key role of ciliates as consumers of phytoplankton biomass. Biomasses of ciliates increased during spring and were highest during summer. Relative importance of mixotrophs were high due to occurrence of Mesodinium rubrum blooms as well as other mixotrophic ciliates in late spring/early summer. M. rubrum biomass had the opposite pattern of the cryptophyte prey Teleaulax spp., and the coupling between the two populations was very strong in late spring. Ciliates that grazed on selected phytoplankton, had a smaller potential grazing impact regarding their biomasses, likely due to food limitation; conversely ciliates that feed on diverse prey items were less constrained by food limitation, and their seasonality appear to be driven by other factors. These findings suggest that the ciliate community structure and dynamics is important in structuring the phytoplankton community on short and seasonal scale.